Pragmatic-Discursive Approach to the Link Between Prepositional Phrases Headed by «Con» and Morphosyntactic Structures (Islas, 2025)
Introduction: The general objective is to describe the semantic-discursive conditions that enable alternations between prepositional phrases headed by con and morphosyntactic constructions such as adverbialized adjectives in -mente, past participles, and gerunds.Methods: This research follows a dual approach: descriptive-empirical and theoretical-analytical. It is framed within the qualitative paradigm, with an emphasis on the analytical description and interpretation of data.Results: The alternations are explained by the requirement of nominal selection, favoring the +abstract feature of the lexical root of nouns accompanying SP-con, the pattern related to the nominal semantics of prepositional terms, and the modalizing function shared by prepositional phrases and their morphological correlates.Conclusions: Prepositional phrases headed by con can alternate with morphological correlates, such as -mente adverbs, participles, and gerunds, while maintaining implicit semantic congruence. This alternation contributes to a meaning that falls within the scope of modality.
Keywords: semantic alternations; morphosintactic structure; adverbial; prepositional phrase; discursive focus